A mini scale batch reactor for the production of palm‑based polyol - Khairiah Haji Badri,; Muhammad Syukri Ngah, (Universiti Kebangsaan Malaysia, 2015)
An investigation on a batch production of palm kernel oil polyol (PKO-p) was conducted via esterification and condensation. The process design was thoroughly studied as a preliminary step for future upscaling. The process variables included necessity of vacuum pump, controlling of heating rate, recording the production time, nitrogen gas flow and agitator speed. About 250 mL PKO-p was successfully synthesized within 3 h. Vacuum pressure was applied to haul out moisture from the system. The control of heating rate and production time are vital to avoid sudden oxidation.